Multinational Companies from Emerging Economies - Goldstein, A. author. aut Link
XXV, 205 p.
Keywords: This comprehensive study of the rise of multinational corporations from emerging economies explores the basis of their success. Andrea Goldstein argues that the history of multinational business offers valuable lessons for the present and shows how emerging multinationals are embedded in dense political, social and ethnic networks.